Sialidases as regulators of bioengineered cellular surfaces - Zamora, Cristina Y (Glycobiology, 2015)
Human sialidases (NEUs) catalyze the removal of N-acetyl neuraminic acids from the glycome of the cell and regulate a diverse repertoire of nominal cellular functions, such as cell signaling and adhesion. A greater understanding of their substrate permissivity is of interest in order to discern their physiological functions in disease states and in the design of specific and effective small molecule inhibitors. Towards this, we have synthesized soluble fluorogenic reporters of mammalian sialidase activity bearing unnatural sialic acids commonly incorporated into the cellular glycocalyx via metabolic glycoengineering. We found cell-surface sialidases in Jurkat capable of cleaving unnatural sialic acids with differential activities toward a variety of R groups on neuraminic acid. In addition, we observed modulated structure–activity relationships when cell-surface sialidases were presented glycans with unnatural bulky, hydrophobic or fluorinated moieties incorporated directly via glycoengineering. Our results confirm the importance of cell-surface sialidases in glycoengineering incorporation data. We demonstrate the flexibility of human NEUs toward derivatized sugars and highlight the importance of native glycan presentation to sialidase binding and activity. These results stand to inform not only metabolic glycoengineering efforts but also inhibitor design.